Ptaki Tarjei Vesaasa w adaptacji Witolda Leszczyńskiego. O genezie arcydzieła filmowego - Bukowski, Piotr de Bończa (Folia Scandinavica Posnaniensia, 2016)
One of the masterpieces of Polish cinema is the debut film by Witold Leszczyński The Days of Matthew (1967, Żywot Mateusza). It is an adaptation of the novel Fuglane by Tarjei Vesaas, which appeared in translation into Polish in 1964. Leszczyński’s awarded film work has become an object of numerous analyses. However, there has been no particular research on the origins of The Days of Matthew. This article aims at presenting and interpreting the genesis of the film, viewed from three different perspectives: the existential, the ethical and the technical one. The study is largely based on previously unknown information or rarely cited sources.